Vitamin D Status Across Age Groups in Turkey: Results of 108,742 Samples from a Single Laboratory - BEREKET, ABDULLAH (GALENOS YAYINCILIK, 2020)
Objective: The aim was to determine vitamin D status in the general population in Turkey between 2011 and 2016, and to evaluate the effectiveness of the national vitamin D supplementation programme. Methods: Serum 25-hydroxyvitamin D (25-OHD) measurement data were retrieved from an internationally accredited laboratory, operating nationwide. A total of 108,742 measurements of 25-OHD were analyzed using the cut-off values of 0-11 ng/mL, 12-19 ng/mL, 20-49 ng/mL, 50-70 ng/mL and > 70 ng/mL for vitamin D deficiency, insufficiency, sufficiency, possibly harmful and excess respectively. Results: The mean +/- standard deviation 25-OHD level was 21.6 +/- 13.3 ng/mL. Mean 25-OHD concentrations by age groups were: 37.3 ng/mL, 30.1 ng/mL and 23.7 ng/mL for <1, 1-10 and 11-18 year old groups, respectively. Mean 25-OHD levels of children <1 year and 1-3 years of age were significantly higher than those found in other age groups. The prevalence of vitamin D deficiency (<12 ng/mL) was lowest in children at 1-3 years of age (5%). In subjects older than 18 years of age, mean 25-OHD levels were 18.2 ng/mL, 20.1 ng/mL, 21.9 ng/mL and 21.1 ng/mL for age groups 19-30, 31-50, 51-70 and >70 years, respectively. Conclusion: Successful implementation of the national vitamin D supplementation programme, appears to have nearly eliminated vitamin D deficiency for children under I-years of age. However, the positive impact of the vitamin D supplementation diminishes as children get older suggesting that supplementation may be required in the older children and adults. In addition, improved awareness of the benefits and risks of excess vitamin D should prevent unnecessary and excessive use of vitamin D supplements.
Keywords: Vitamin D; deficiency; National Prophylaxis Program; 1 year of age; D DEFICIENCY; PREVENTION; CHILDREN